ANALYSIS OF NON-TRADITIONAL ADDITIVES USED IN THE PRODUCTION OF BAKERY PRODUCTS - Y. A. Timanovskiy (Современная наука и инновации, 2022)
The analysis of food non-traditional additives that are used to improve the physico-chemical, organoleptic and consumer qualities of bakery products. Various additives that increase the nutritional and energy value of bread have been studied.